2006
DOI: 10.2135/cropsci2005-05-0046
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Effects on Nitrogen Use Efficiency of Spring Cereals under Northern Conditions

Abstract: Spring cultivars of barley (Hordeum vulgare L.), oat (Avena sativa L.), and wheat (Triticum aestivum L.) are the most important crops in Finnish agricultural systems. The increasing need to reduce pollution from N fertilizer is concomitantly strengthening the importance of improving the understanding of nitrogen use efficiency (NUE) of these crops. The aim of this work was to study the differences in NUE, defined as the crop's ability to produce yield with one available N unit, among spring cereal cultivars, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
65
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 34 publications
(46 reference statements)
11
65
1
3
Order By: Relevance
“…A wide range of studies has been carried out in the last few years; their common purpose has been to determine the changes in efficiency of varieties during the breeding process, and changes in the efficiency of the exploitation of nutrients. Muurinen et al (2006) studied the efficiency of the exploitation of nitrogen in wheat, oat and barley, bred in Finland between 1909 and 2002. Modern varieties of wheat and oat were more efficient, they absorbed more nitrogen and were able to use it more efficiently than the older ones.…”
Section: Nutrient Uptake and Utilization Efficiencymentioning
confidence: 99%
“…A wide range of studies has been carried out in the last few years; their common purpose has been to determine the changes in efficiency of varieties during the breeding process, and changes in the efficiency of the exploitation of nutrients. Muurinen et al (2006) studied the efficiency of the exploitation of nitrogen in wheat, oat and barley, bred in Finland between 1909 and 2002. Modern varieties of wheat and oat were more efficient, they absorbed more nitrogen and were able to use it more efficiently than the older ones.…”
Section: Nutrient Uptake and Utilization Efficiencymentioning
confidence: 99%
“…Hence, increased interest is being shown worldwide in cultivars that are more efficient in utilizing soil resources and better fitted to water and nutrient limitations (El Bassam 1998;Good et al 2004;Fageria and Baligar 2005;Phillips and Wolfe 2005;Muurinen et al 2006;Hirel et al 2007; Lammerts van Sylvester-Bradley and Kindred 2009). Among cereals, hexaploid winter wheat (Triticum aestivum L.) is commonly identified as a species with higher requirements for nutrients, especially nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the result of the current correlation analysis of fertilizer level with higher biomass yield and harvest index could result in higher grain yield of maize. In other similar studies, different authors also reported positive correlations among certain growth and yield parameters of maize (Loffer et al, 1985;Van Sanford and MacKown, 1986;Sinebo et al, 2004;Muurinen, 2007).…”
Section: Harvest Index (Hi)mentioning
confidence: 60%